The Emphasized Legislative in Macedonia Institutions and Enforce Laws, Regulations and Developing Administrative Improvements - Sinani, Blerton; Dumi, Alba (Mediterranean Journal of Social Sciences, 2012)
The definition of the constitutional law is an important theoretical problem, because in literature, generally, "there isno single definition" of the constitutional law. Seen from the perspective of the broad (wide) comparative juridical-constitutionalliterature, a conclusion drawn can be, that the constitutional law can be defined in two main meanings: first, in the traditionalmeaning and, secondly, in the modern one. In the traditional sense, the constitutional law is defined as "a set of juridical normsthat refer to the dispersion of state power and the exercise of that power by the state bodies and with which in the same time thereciprocal relationships within state bodies, and the reciprocal relationships between state, citizens and institutions are defined."In the frame of the traditional sense, the constitutional law can be viewed in two basic meanings (senses) one, in the strictmeaning and, two, in the broad one. In its narrowest sense, the constitutional law can be defined as "a set (an entirety) ofjuridical norms, intended to regulate relationships within the state between the ruler (ruler) and the governed (ruled).